Analysis and implementation of SQL injection attack and countermeasures using SQL injection prevention techniques. (5th September 2022) - Jesudoss, A.; Mercy, Theresa M.; Christy, A.; Maheswari, M.; Selvi, M.; Ulagamuthalvi, V.
SQL injection attack is the most critical and very common attack to security of web applications. The paper analyses the vulnerabilities that arise due to SQL injection attacks and presents consolidated prevention techniques which consider all vulnerabilities and identifies the SQL injection attacks. It also provides appropriate solution for safeguarding against SQL injection attacks. While being cost-effective, these prevention techniques are also easy to configure, administer and implement. Experimental results have proven that these prevention techniques efficiently identify and protect against SQL injection attacks. The prevention techniques discussed in this paper have been implemented and tested effectively. The results of testing are satisfactory.